Effect of polyoxoanions and amide group coordination modes on the assembly of polyoxometalate-based metal–organic complexes constructed from a semi-rigid bis-pyridyl-bis-amide ligand. Issue 4 (4th December 2014) - Wang, Xiuli; Chang, Zhihan; Lin, Hongyan; Tian, Aixiang; Liu, Guocheng; Zhang, Juwen; Liu, Danna
Abstract : Four polyoxometalate-based metal–organic complexes constructed from a semi-rigid bis(pyridylformyl)piperazine ligand have been synthesized and characterized. Abstract : A series of polyoxometalate (POM)-based metal–organic complexes constructed from a semi-rigid bis-pyridyl-bis-amide ligand have been hydrothermally synthesized and structurally characterized: [Cu2 L2 (PMo VI 11 Mo V O40 )(H2 O)2 ]·2H2 O (1 ), [Cu2 L2 (PW VI 11 W V O40 )(H2 O)6 ]·H2 O (2 ), [Cu2 L2 (SiW12 O40 )(H2 O)6 ]·H2 O (3 ) and [Cu2 L2 (H2 K2 Mo8 O28 )(H2 O)2 ] (4 ) (L = N, N ′-bis(3-pyridinecarboxamide)-piperazine). Single-crystal X-ray analyses reveal that complex1 is a 2D metal–organic architecture based on the Keggin-type [PMo VI 11 Mo V O40 ] 4− anions and quadrate Cu2 L2 loops. Isostructural complexes2 and3 display 2D supramolecular networks based on 1D infinite chains, which are constructed from quadrate Cu2 L2 loops and Keggin polyoxoanions. Complex4 exhibits a 3D metal–organic framework derived from the newly-reported [K2 Mo8 O28 ] 6− polyoxoanions and quadrate Cu2 L2 loops. The L ligands show a μ3 -bridging coordination mode ( via ligation of two pyridyl nitrogen atoms and one carbonyl oxygen atom) in1 and4, and a μ2 -bridging coordination mode ( via ligation of two pyridyl nitrogen atoms) in2 and3, forming Cu2 L2 loops in1–4 . The influence of amide group coordination modes and structural features of POMs on the structures of the title complexes has been discussed. The electrochemical properties and selective photocatalytic properties of the title complexes have been reported in this article.